NIMG-55. TO ASSESS THE UTILITY OF ADVANCED QUANTITATIVE DIFFUSION MRI DERIVED FROM MULTI B VALUE ACQUISITIONS IN THE ASSESSMENT OF TREATMENT RESPONSE, USING A SPATIALLY-INDEPENDENT APPROACH. (11th November 2019) - Islam, Shah; Morrison, Melanie; Waldman, Adam
Abstract: PURPOSE: To assess the utility of advanced diffusion MRI derived from multi b value acquisitions in the assessment of treatment response, using a spatially-independent approach. METHOD AND MATERIALS: 13 GBM patients were enrolled into our multicentre study. All patients completed RT with TMZ. Imaging was performed pre-RT and mid RT. The MRI protocol included a 'low' b value acquisition (b= 0s/mm, 50s/mm, 150s/mm, 200s/mm, 500s/mm, 1000s/mm) from which monoexponential diffusion indices ADC and biexponential indices, IVIM parameters D*, D and f were calculated. A 'high b value' acquisition (b=0 s/mm, 500s/mm, 1000s/mm, 1500s/mm, 2000s/mm, 2500s/mm, 3000s/mm, 3500s/mm, 4000s/mm) was acquired to allow stretched exponential diffusion indices, DDC and alpha to be derived. FLAIR sequences were used to define ROI and clinical assessment of mid-treatment and end-treatment response using RANO criteria. Histograms were generated from voxels located within manually segmented ROIs defined by increased signal on T2 FLAIR images. Changes in histogram percentile profiles were evaluated across the two timepoints and compared with RANO assessment at the mid treatment and end treatment timepoints. RESULTS: Following completion of treatment, 5 patients had PD, 4 SD and 4 CR. Patients with PD showed a histogram shift to the left across all diffusion models, in keeping with increasing diffusion restriction and implying increased cellularity. Patients with SD or CR showed little or no shift in the histogram. DDC and f are the most predictive of progression against RANO assessment, and appear superior to routine ADC. Reduction in 75th centile (f) and 95th centile (DDC) are the most sensitive histogram metrics for predicting early progressive disease. CONCLUSION: Results suggest association between early changes in specific diffusion components and subsequent treatment response. Spatially-independent diffusion parameter comparisons provide unbiased sampling of tumour heterogeneity and abrogate the confound of voxel-to-voxel misregistration due to tumour growth/shrinkage.